MEAN CHANGES IN SPERM COUNT IN ADULT MALES AFTER VARICOCELECTOMY - Khan, Imranuddin; Qayyum, Abdul; Khan, Nadim; Akhtar, Muhammad Shaheer; ullah, Tahir; Imran, Sadaf (Journal of Postgraduate Medical Institute, 2020)
Objective: To determine changes in the sperm count in adult males with clinically palpable varicocele after varicocelectomy. Methodology: This quasi experimental research was performed in 174 adult male patients with clinically palpable varicoceles at the department of general surgery, Lady Reading Hospital (LRH) Peshawar from January 2016 to January 2017. Adult males with clinically palpable varicocele were selected with consecutive sampling. Inguinal varicocelectomy was performed by consultant surgeon after obtaining written informed consent. Sperm count was done before and after the procedure. Data was entered in SPSS version 20.0 and was analyzed using descriptive statistics. Paired t- test was applied to compare mean change in pre-operative and post-operative sperm count. Results: Mean age was 39 ± 10.37 years. Mean pre-operative sperm count was 15 ± 17.880 million, while mean post-op sperm count was 34 ± 13.149 million indicating change of 5 ± 9.95 million. The difference was statistically significant (p =0.0001). Conclusion: Sperm count in adult patients with clinically palpable varicocele increases after inguinal varicocelectomy.